Tanggung Jawab Pengangkut Mengenai Pengangkutan Barang Mealui Laut - Harto Harto (CV. Syntax Corporation Indonesia, 2023)
Sea transportation is the most important means of connecting one island to another in Indonesia, most of which consists of water. The obligation of the Carrier is to organize the transportation and maintain the safety of the Goods from the time they are received until they are handed over to the Recipient. From this obligation arises the responsibility of the carrier because the carrier must maintain the safety of the goods he transports, so everything that interferes with the safety of the goods he transports is the responsibility of the Carrier. This research on the responsibility of the Carrier uses a descriptive analytical research method, while the type of research is a normative research type. This research on the responsibility of the Carrier in the Transportation of Goods by the Sea is intended to answer problems regarding the system of responsibility used by the Carrier and the legal basis governing the Responsibility of the Carrier. The results of the research from the author show that the carrier's responsibility system and its restrictions cannot be separated from the provisions contained in the KUHD, especially Article 468 of the KUHD and the rules contained in the Bill of Lading.